To give birth and to be born. Body traces, subjective impact and violated rights - Arnao Bergero, Magdalena; Galván, Virginia Luz; Roso, Flavia (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2018)
In our country, hospital care during childbirth is highly medicalized and interventionist, and leaves aside subjective aspects of those who are protagonists. In this paper, we analyze the reasons that make this scenario possible, despite the existence of an extensive legal framework and vast scientific evidence that show the negative effects of this model. These practices reflect the patriarchal logics which underlie the relational social fabric of our society and one of the many forms that gender violence adopts today. Considering birth as a deeply subjective, significant and singular event, we draw attention to the possible emotional consequences and subjective traces that result from the dominant attention model. In addition, we highlight the urgent need for a change of paradigm in order to install respected childbirth as the norm and as an event to take care of and protect in relation to the mental health of the whole society.